1991
DOI: 10.1210/jcem-72-2-422
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Training Decreases Serum Testosterone Levels in Men without Change in Luteinizing Hormone Pulsatile Release*

Abstract: Cross-sectional studies have suggested that total and bioavailable testosterone levels are reduced in some male athletes. Such changes may be related to loss of body weight, increased serum cortisol, and/or alterations in LH pulsatile release. To determine how endurance training may affect androgen levels, we measured serum total testosterone, sex hormone-binding globulin, free androgen index, LH, FSH, PRL, cortisol, and weight in 15 previously sedentary males. We also examined pulsatile LH release in a subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
75
3
19

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 10 publications
13
75
3
19
Order By: Relevance
“…This alteration was associated with a decrease in the FAI, which represents the biologically active form of the hormone. Neither of the hormonal changes was induced by modification of the SHBG level, as previously demonstrated by various authors [20, 24]. …”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This alteration was associated with a decrease in the FAI, which represents the biologically active form of the hormone. Neither of the hormonal changes was induced by modification of the SHBG level, as previously demonstrated by various authors [20, 24]. …”
Section: Discussionsupporting
confidence: 69%
“…Alterations in androgens have often been described in the literature on endurance athletes, particularly in marathon runners. However, although low, the values of TT and FT have always been within the normal range [18, 19, 20, 21, 22, 31]. Other authors [23, 24, 27], and Lucia et al [25]especially, have found normal T levels in male endurance athlete groups composed of marathon runners, professional CY and elite TR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence indicates a role for aerobic physical activity in SHBG production, at least in men. SHBG concentrations have been observed to increase acutely with such exercises as cycle ergometry, and with longer-term endurance training (38)(39)(40)(41), although some reports involving endurance-trained younger men have not confirmed this effect (18,21,37,42). As SHBG concentrations vary inversely with circulating insulin (43), a plausible explanation for greater SHBG values in trained older men could be attenuation of agerelated insulin-resistance.…”
Section: Journal Of Endocrinology (1998) 138mentioning
confidence: 99%
“…Several authors have reported lower concentrations of both total testosterone (17,18) and free testosterone (19,20) in young endurance-trained men compared with age-matched 'sedentary' controls, whereas others have observed no effect of endurance exercise on total testosterone concentrations (21,22). Even if habitual endurance activity were to improve IGF-I production, an exercise-dependent attenuation of gonadal function might negate any potential benefits of the former on body composition.…”
Section: Introductionmentioning
confidence: 99%